Student Leadership and Improvement of Tertiary Institutions in Nigeria - Abdullahi, Nimota Jibola Kadir (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2022)
Abstract The main objective of this research was to determine how students’ leadership affected improvement of tertiary institutions. Total of 400 participants were selected purposefully from the sample universities in Kwara State. The findings of the study shown that students’ welfare services, information dissemination and sport development enhanced effective improvement of university education. Pearson product moment correlation coefficient and linear regression analysis were used to test the hypotheses. Therefore, it was recommended that tertiary institutions authorities should continue to improve students’ welfare services so as to motivate learners to learn, encourages freshers to get acquainted with school programs through orientation activities. Also, university authorities should encourage effective dissemination of information to make school life easy ad comfortable for students. Furthermore, school authority should continue to encourage development of sport activities in order to help helps student to manage emotions, develops students’ self-esteem and self-confidence as well as makes students to be disciplined so as to enhance effective school improvement. Keywords: leadership; students’ welfare services; information dissemination; improvement